2017
DOI: 10.1002/capr.12151
|View full text |Cite
|
Sign up to set email alerts
|

Women's experiences of the therapeutic value of writing about pregnancy sickness

Abstract: Background There is evidence of the beneficial effects of writing therapy in relation to a range of disorders. This is the first study to evaluate those effects in the field of pregnancy sickness. Aim To analyse the experiences of women using writing therapy to address issues associated with pregnancy sickness. Method Ten women with an age range of 32–48 years participated in this research study. All had been hospitalised at least once with severe pregnancy sickness symptoms in the form of hyperemesis gravidar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Question two contained the most qualitative studies with six identified describing women’s experiences of the condition and its treatments 55–60…”
Section: Results Per Questionmentioning
confidence: 99%
See 2 more Smart Citations
“…Question two contained the most qualitative studies with six identified describing women’s experiences of the condition and its treatments 55–60…”
Section: Results Per Questionmentioning
confidence: 99%
“…[52][53][54] Question two contained the most qualitative studies with six identified describing women's experiences of the condition and its treatments. [55][56][57][58][59][60] Question 3: what causes HG? Seventy-one studies have attempted to find a cause for HG.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnancy sickness specific counselling may be helpful either during or after pregnancy. 173 Measures that address NVP, poor social support and depression are warranted throughout pregnancy. 112 A prospective cohort study of 367 women suggests that practitioners could improve their management of NVP by addressing symptoms and life situation.…”
Section: [Evidence Level 2++]mentioning
confidence: 99%
“…Therapeutic writing can be conceptualised as writing in a structured or unstructured manner, which can be guided or self‐initiated, and facilitates the expression, exploration and reflections upon emotions and thoughts relating to an objective experience (Wright & Chung, 2001). Sometimes referred to as “expressive writing,” its overall focus is to improve mental or physical well‐being, with a growing recognition of the value in writing for therapeutic purposes as a credible therapeutic intervention (Nicholson, 2018). A seminal study by Pennebaker and Beall (1986) created the expressive writing paradigm and published the starting point of experimental studies for a growing field of enquiry (Nicholls, 2009).…”
Section: Introductionmentioning
confidence: 99%